Pengaruh Kecanduan Internet Dan Future Time Perspective Terhadap Prokrastinasi Akademik Dikalangan Pelajar - Nurul Afifah Asyifak (Universitas Muhammadiyah Malang, 2023)
Academic procrastination is the behavior of procrastinating, doing, or completing academic assignments. Academicprocrastination among students can result in academic failure, not even dropping out of classes. This research aimed to determine the influence of Internet addiction and the future perspective on academic procrastination among students. This research was quantitative research with junior high school student research subjects. The measurement tool used is the Young Internet Addiction Diagnostic Questionnaire, the are Procrastination Scale, and the Future Time Perspective for Adolescents and Young Adults. Analysis data using multiple linear regression analysis. This research obtained the coefficient of determination (R² ) at 0.426 and F Sig. 0.000¡0.050. From the results of the t-test, it was found that there was a significant positive effect between addictions internet with academic procrastination with a value of t = 5.641, and there is a significant negative effect between future perspective and academic procrastination with a value of t = -11.543. The beta value in the absolute price for Internet addiction is 0.262, and the beta value for the future time perspective is 0.536, so it can be concluded that the coming time perspective has more influence on academic procrastination.